The Implementation of Project Based-Learning as ISMUBA Curriculum Development in Muhammadiyah Schools - Hendro Widodo,; Sulastri,; Mohammad Jailani,; Miftachul Huda, (TADRIS: Jurnal Pendidikan Islam, 2024)
The ISMUBA curriculum is a unique curriculum which used holistic-integrative matters. In a student-centered learning era, the existence of such curriculum is important and meaningful especially combine with project-based learning. Therefore, this study aims to explore project-based learning, as a development of the holistic-integrative ISMUBA curriculum. This research was conducted at SD Muhammadiyah Sapen Yogyakarta. This research approach is qualitative research based on field studies. The subjects of this study consisted of teachers and students. Data were obtained by interview, observation, and documentation methods. Data analysis was carried out using three steps namely display, reduction, and verification techniques. The results of the study were obtained. Project-based learning is an important component in developing the ISMUBA curriculum at SD Muhammadiyah Sapen Yogyakarta. The concepts built in project-based learning encourage students to think critically, creatively, and innovatively to support 21st-century learning skills that are relevant to UNESCO concepts. Learning to know and learning to do are teaching developments that improve students' critical thinking, creativity, innovation, and problem-solving. This research implies that the development of the ISMUBA curriculum is the answer to the four-pillar learning targets issued by UNESCO.